Aerodynamics effects of APC slow flyer propeller blade design with different airfoil origin positions - Ahmad Faris, Ahmad Fariduddin; Basri, Adi Azriff; Basri, Ernnie Illyani; Hameed Sultan, Mohammed Thariq; Ahmad, Kamarul Arifin (Zhongguo Hangkong Taikong Xuehui, 2022)
This paper presents a numerical method investigation on the aerodynamic performance of a small-scale propeller with four different shapes of propeller design using computational fluid dynamic (CFD). In this study, the relationship between varying airfoil's origin position (AOP) at each station and resultant aerodynamics performance is investigated. Several designs of the propellers are derived by changing the AOP at each blade station with the percentage of 0% AOP, 25% AOP, 50% AOP, 75% AOP and 100% AOP. The result of thrust, power coefficients and efficiencies are validated with the existing experimental wind tunnel data. All in all, the results show that propeller design with 100% AOP generates better aerodynamic performance than the one with 25% AOP by 7.473%, -5.587% and 15.891% in terms of thrust, coefficient of power and efficiency, respectively. It has also been found that the propeller design with 100% AOP has a better aerodynamics performance compared to the 25% AOP, 50% AOP and 75% AOP, especially at an advanced ratio of 0.799. Overall, it can be concluded that the improvement in terms of aerodynamic characteristics and performance is possible by increasing the position of the blade origin at each station, which in turn results in different propeller design shapes.